1998
DOI: 10.4315/0362-028x-61.7.865
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Bifidobacterium Strains for Probiotic Formulation

Abstract: Twenty-five Bifidobacterium strains isolated from infant feces were identified by sugar fermentation patterns and whole-cell protein analysis. Using gradient SDS-PAGE, six characteristic protein bands of the genus were detected in 40 strains of bifidobacteria but not in lactobacilli. Computerized numerical analysis enabled strains to be grouped in two main clusters. Strains of Bifidobacterium bifidum belong to a well-differentiated cluster that joins the cluster of the remaining species at 0.582 similarity. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0
14

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 0 publications
8
49
0
14
Order By: Relevance
“…Probiotic lactobacilli are required to pass through the highly acidic gastric condition of the stomach in order to reach the intestine for residence and functioning, and hence such strains must be tolerant to low-pH conditions of the stomach and resistant to intestinal bile salts for their survival in the digestive system, because viability and activity are important considerations of microorganisms to be the probiotics [22]. The physiological concentration of human bile salts ranges 0.3-0.5% [23,24]. Considering bile tolerance an important characteristic of probiotic microorganisms, it has been reported that 0.3% oxgall closely appropriates the bile level of the human gastrointestinal tract, and the concentration of 0.3% bile salts has been considered crucial for screening and selection of human probiotics [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic lactobacilli are required to pass through the highly acidic gastric condition of the stomach in order to reach the intestine for residence and functioning, and hence such strains must be tolerant to low-pH conditions of the stomach and resistant to intestinal bile salts for their survival in the digestive system, because viability and activity are important considerations of microorganisms to be the probiotics [22]. The physiological concentration of human bile salts ranges 0.3-0.5% [23,24]. Considering bile tolerance an important characteristic of probiotic microorganisms, it has been reported that 0.3% oxgall closely appropriates the bile level of the human gastrointestinal tract, and the concentration of 0.3% bile salts has been considered crucial for screening and selection of human probiotics [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Bile reduces the number of bacteria by destroying their cell walls. The concentration of bile salts in the human body is 0.3-0.5% [18][19][20], and several probiotic bacteria have been shown to survive these concentrations [21], found Lactobacillus oris HM168 isolated from breast milk, survives at 0.3% and 0.5% bile salt for 5 h. Likewise, the strain of lactic acid bacteria isolated from buffalo milk from Karnataka, India, was able to survive in concentrations of 0.3% and 0.5% bile salts, but this was not sustained at 1% [2]. The five isolates of lactic acid bacteria were tested for bile salt resistance of 0.3% and 0.5%, for 5 h. Fig.…”
Section: Lactic Acid Bacteria Resistance Against Bile Saltsmentioning
confidence: 99%
“…Similarly, bile plays a fundamental role in specific and non-specific defense mechanisms in the gut; the magnitude of its anti-pathogen effects is determined primarily by the concentration of its bile salts (Charteris et al, 1998). Relevant salt levels in human bile range from 0.3-0.5% (w/v) (de Smet et al, 1998;Zavaglia et al, 1998). In the study here, there was resistance to toxicity from bile salts by the L. plantarum MON03; this finding supports the importance of assessing bacterial tolerance to bile when selecting potential agents to be used for in situ detoxification processes in the gut.…”
Section: Discussionmentioning
confidence: 99%